Optimizing Organizational Performance in Bridge Maintenance using Stakeholder Analysis - Karim, Rully Andhika; Laksono, Naufal Budi; Ardiyanto, Fahreza; Latief, Yusuf; Trigunarsyah, Bambang (Jurnal Teknik Sipil dan Lingkungan, 2025)
Bridge maintenance and care is an important aspect in maintaining the safety and efficiency of transportation infrastructure. However, challenges in coordination between various stakeholders often hamper operational effectiveness. This study aims to analyze the organization of bridge maintenance and care work using a stakeholder analysis approach, in order to improve organizational performance. The methods used in this study are qualitative and quantitative approaches, involving data collection through in-depth interviews and surveys of stakeholders, including the government, contractors, and user communities. The data obtained were analyzed to identify factors that influence organizational performance in bridge maintenance. The results show that active stakeholder involvement and effective communication contribute significantly to increasing efficiency and effectiveness in the bridge maintenance process. This study confirms that the application of stakeholder analysis can improve organizational performance in bridge maintenance by strengthening relationships between stakeholders and responding to their needs and expectations. Practical recommendations for the implementation of this strategy are presented, including the importance of communication training and collaboration between stakeholders. This study is expected to contribute to the development of policies and best practices in bridge infrastructure maintenance in the future.